2003
DOI: 10.1063/1.1567461
|View full text |Cite
|
Sign up to set email alerts
|

Negative bias temperature instability: Road to cross in deep submicron silicon semiconductor manufacturing

Abstract: Articles you may be interested inInterface traps responsible for negative bias temperature instability in a nitrided submicron metal-oxidesemiconductor field effect transistor Appl. Phys. Lett. 98, 103513 (2011); 10.1063/1.3559223 Bias temperature instability in metal-oxide-semiconductor field-effect transistors with atomic-layer-deposited Sinitride/ Si O 2 stack gate dielectrics J. Appl. Phys. 103, 084512 (2008); 10.1063/1.2907768Using the Hall effect to measure interface trap densities in silicon carbide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
408
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 940 publications
(426 citation statements)
references
References 81 publications
13
408
2
3
Order By: Relevance
“…It has been observed that the effect of NBTI becomes more severe because of the introduction of nitrogen into the gate dielectric which is done primarily to reduce the boron penetration from P+ poly gate into the thin oxide and also for reducing the gate leakage [5]. Criterion for the device failure is still a debatable topic, Schroder et al [6] proposed that device failure criteria is often benchmarked at v th shift of 50 mV or ΔI ds /I ds ~ 10% but still it is circuit dependent.…”
Section: Nbti Degradation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the effect of NBTI becomes more severe because of the introduction of nitrogen into the gate dielectric which is done primarily to reduce the boron penetration from P+ poly gate into the thin oxide and also for reducing the gate leakage [5]. Criterion for the device failure is still a debatable topic, Schroder et al [6] proposed that device failure criteria is often benchmarked at v th shift of 50 mV or ΔI ds /I ds ~ 10% but still it is circuit dependent.…”
Section: Nbti Degradation Mechanismmentioning
confidence: 99%
“…As discussed in [8] the interfacial traps density in case of H 2 only diffusion is given by- (6) with time exponent of (n = 1/6).…”
Section: H H H  (4)mentioning
confidence: 99%
“…On JEDEC Standard JEP122G, reliability models as Electromigration [32], Ohmic contact degradation [33] [44], NBTI [45] are generally expressed by a function of stress parameter or by a function of an electrical predictor multiplying the exponential activation energy factor.…”
Section: Reliability Mathematics and Toolsmentioning
confidence: 99%
“…NBTI occurs when PMOS transistors are negatively biased (i.e., V gs = −V dd ) at elevated temperature, causing a shift in threshold voltages. Over a long period of time, such V th shifts can potentially cause a significant increase in the delay of PMOS devices [2], and result in about 10-20% degradation in cir- 1 This work was supported by National Natural Science Foundation of China (No. 60870001, No.90207002) and TNList Cross-discipline Foundation.…”
Section: Introductionmentioning
confidence: 99%